Concept of the Life Cycle of Innovation - NECHAEV, Andrey S.; ANTIPINA, Oksana V. (Journal of Advanced Research in Law and Economics; Vol 7 No 3 (2016): JARLE, Volume VII, Issue 3(17), Summer 2016, 2016)
The economic transition of a country to an innovative way of development is impossible without the formation of a competitive, at a global scale, national innovation system. Thus, this research is aimed at the establishment of the innovation life cycle concept as a part of innovation development planning. The proposed scheme allows a particular company to analyze the economic activity, both from a present-day perspective and in the context of further development prospects. It is based on the correlation between the cost of research and evaluation of performance at the stages of innovation and reinvestment areas depending from the volume of sales and from the demand for innovative products in the course of use and maintenance thereof. Moreover, the authors have submitted the integrated model for determining the cost of the product life cycle stages, taking into account the fiscal (tax and customs) payments and foreign trade activities of innovation-active business entities.